KEMANDIRIAN KEUANGAN DAERAH DAN PERTUMBUHAN EKONOMI KABUPATEN/KOTA LAMPUNG TAHUN ANGGARAN 2014-2018 - Afif, Fadeli Yusuf; Ciptawaty, Ukhti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
This study aims to analyze the independence and ability of regencies / cities and their effects on economic growth in Lampung Province. The method used is panel data analysis. The results showed that Bandar Lampung City was in a consultative relationship pattern, while 13 districts and 1 other city were in an instructive relationship pattern. Whereas based on the analysis of regional financial capability, Bandar Lampung City has a good relationship pattern category, the Metro City category of sufficient relationship pattern and South Lampung Regency and East Lampung Regency with less relationship pattern criteria. Whereas the other 11 districts are still in very poor category. Regression results show that the ratio of regional financial capacity has a negative and significant effect on the level of ? (5%) on economic growth, while regional financial independence has no effect on economic growth.